Substitute names for three genera of fossil Neuroptera, with taxonomic notes - Makarkin, Vladimir N.; Archibald, S. Bruce (Zootaxa, 2005)
The names of three genera of fossil Neuroptera are found to be junior homonyms; we propose the following substitute names: Glottopteryx nom. nov. for Glottidia Bode, 1953; Hongosmylites nom. nov. for Sinosmylites Hong, 1996; and Jurosmylus nom. nov. for Mesosmylus Panfilov, 1980. The family-group name Glottidiidae Bode, 1953 is unavailable and should be considered nomen nudum. The spelling of the family name Osmylopsychopidae Martynova, 1949 (not Osmylopsychopsidae) is grammatically correct and available. The family affinities of these fossil genera are briefly discussed: Glottopteryx may belong to Prohemerobiidae or Osmylopsychopidae; Hongosmylites to an undetermined psychopsid-like family; Jurosmylus with confidence to Osmylidae; Sinosmylites Hong, 1983 is most probably a member of Prohemerobiidae.